A question of impact: Did we underestimate the consequences of the sixteenth and seventeenth centuries period of early European exploration in the Pacific?. (2nd October 2021) - Cruz Berrocal, María; Sand, Christophe
Abstract: Historical narratives on Oceania have over the last two centuries mainly focused on the second half of the eighteenth century as the significant period of first encounters between Pacific Islanders and Western explorers. However, the first crossing of the region by Fernando de Magallanes (Ferdinand Magellan) was in 1521. More importantly, it has been widely neglected that during the sixteenth and seventeenth centuries, Spanish, Dutch, and Portuguese explorers navigated through parts of Polynesia, Melanesia, and Micronesia, making regular landfalls and contact with many islands and archipelagos. The potentially devastating consequences of these early encounters (i.e., with interpersonal violence between natives and newcomers as well as the potential introduction of new deadly diseases) are well known for islands like Guam. They possibly also influenced the cultures and traditions of other archipelagos of Oceania before the better known voyages of Cook, La Perouse, and others more than 150 years later. Drawing on historical data and the scarcely available archaeological evidence, this paper aims to show that there is an urgent need to reconsider the early phase of Pacific-Western contacts as a key period in the shaping of the "traditional" indigenous cultural behaviors in parts of Oceania. This assessment has the potential to profoundly change our understanding of the ethnographical observations of the eighteenth and early nineteenth centuries that have been produced and used in the last two centuries to define a baseline of the beginning of Western impacts on Indigenous societies in the region.